Appraisal of ionic contamination in water of the Bangshi river for irrigation usage towards food safety (Journal of the Bangladesh Agricultural University, 2020)
Ionic contamination has become a serious environmental problem due to long-term disposal of untreated industrial effluent containing metal ions in river water ecosystem when applied to soil system as irrigation water. Considering this issue, an attempt was made to explore ionic contamination in water samples collected from the adjacent crop fields irrigated with the contaminated river during dry season towards food safety. Fifteen water samples were collected randomly from the upstream to downstream of the Bangshi river to determine ions in order to categorize these samples on the basis of their applicability for irrigation usage. The chemical analyses included pH, electrical conductivity (EC), total dissolved solids (TDS), cations (Ca, Mg, K, Na, Cd, Cr & Mn) and anions (CO3, HCO3, Cl & PO4). pH values of river water samples ranged from 6.5 to 7.6 indicating slightly acidic to slightly alkaline in nature. All the water samples were categorized as fresh water (TDS